Informal online communities and networks as a source of teacher professional development: A review - Macià, Maria; García, Iolanda (Teaching and Teacher Education, 2016)
Informal online communities and networks offer teachers the possibility of voluntarily engaging in shared learning, reflecting about teaching practice and receiving emotional support. Bottom-up online communities and networks are an important source of professional development, although research around these social learning structures mainly consists in describing particular cases using a wide diversity of theoretical and methodological approaches. This review analyses the existing theoretical frameworks and methodological approaches, the main characteristics and practices of online communities and networks, as well as their principal repercussions in teacher professional development. A critical analysis of the emergent themes in the revised articles sheds light on eligible perspectives for further research.
Keywords: In-service teacher education; Informal learning; Online community; Online social network; Professional development